Relationship between inhibition performance of melamine derivatives and molecular structure for mild steel in acid solution. (1st August 2017) - Liao, Liu Li; Mo, Shi; Luo, Hong Qun; Feng, Yu Jun; Yin, Hong Yao; Li, Nian Bing
Highlights: Five similar melamine derivatives were employed as corrosion inhibitors. Their inhibition performances were evaluated experimentally and theoretically. The inhibition effects were correlated to their molecular structures. The effects of number and chain length of substituent were discussed. Abstract: The influence of substituent groups on the inhibition performance of the heterocyclic ring is attractive in the field of corrosion inhibitor. The modification of various polar functional groups including dimethylamino ethyl and dimethylamino propyl groups on melamine ring can endow these compounds with good water solubility and even high corrosion inhibition efficiency. The inhibition properties of five functional melamine compounds with methyl and different numbers of tertiary amino groups were investigated electrochemically and theoretically. The inhibition mechanisms of these inhibitors for mild steel in acid solution and the relationship between their inhibition performances and molecular structures are also discussed.